Toward epistemic justice: An approach for conceptualizing epistemicide in the information professions. Issue 1 (22nd October 2020) - Patin, Beth; Sebastian, Melinda; Yeon, Jieun; Bertolini, Danielle
Abstract: The goal of this exploratory paper is to begin to explicate the concept of epistemicide and articulate its function within the information field. We define epistemicide as the killing, silencing, annihilation, or devaluing of a knowledge system. It is not that we are unaware of the injustices happening within our field, but rather, that we are not in discussion across sub‐fields considering the idea that the collective injustices exist and are problematic on individual and systemic levels. We believe epistemicide happens when several epistemic injustices, such as hermeneutical or testimonial injustices, occur collectively reflecting a structured and systemic oppression of particular ways of knowing. We present epistemicide and epistemic injustice as a concept for understanding and addressing ways knowledge systems are silenced, devalued, or annihilated within library and Information Science (LIS).